2013
DOI: 10.1074/jbc.m113.503391
|View full text |Cite
|
Sign up to set email alerts
|

The TREX1 C-terminal Region Controls Cellular Localization through Ubiquitination

Abstract: Background: Mutations in the TREX1 C-terminal region (CTR) cause human autoimmune disease. Results: The CTR directs TREX1 ubiquitination and interaction with ubiquilin 1. Conclusion: TREX1 ubiquitination and co-localization with ubiquilin 1 are differentially affected in autoimmune disease mutants. Significance: Multiple mechanisms of TREX1 dysfunction include altered covalent modification and diminished catalytic function, resulting in a spectrum of autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 68 publications
(107 reference statements)
0
31
1
Order By: Relevance
“…The TREX1 Lys-66 is also positioned in the dimer to hydrogen bond across the interface to Glu-198 of the opposing protomer. The TREX1 E198K mutation is found in AGS (14,39), and, in this case, the TREX1 E198K/E198K enzyme exhibits DNA degradation activities indistinguishable from the TREX1 WT enzyme (31). However, we recently showed that the TREX1 E198K enzyme is hyper-ubiquitinated, suggesting a novel mechanism for altered TREX1 DNA degradation dysfunction and disease.…”
Section: Analysis Of Dsdna Binding By Trex1 Wt and Trex1mentioning
confidence: 95%
See 2 more Smart Citations
“…The TREX1 Lys-66 is also positioned in the dimer to hydrogen bond across the interface to Glu-198 of the opposing protomer. The TREX1 E198K mutation is found in AGS (14,39), and, in this case, the TREX1 E198K/E198K enzyme exhibits DNA degradation activities indistinguishable from the TREX1 WT enzyme (31). However, we recently showed that the TREX1 E198K enzyme is hyper-ubiquitinated, suggesting a novel mechanism for altered TREX1 DNA degradation dysfunction and disease.…”
Section: Analysis Of Dsdna Binding By Trex1 Wt and Trex1mentioning
confidence: 95%
“…The TREX1 mutant enzymes that cause human disease exhibit a broad range of DNA degradation activities that vary from levels indistinguishable from WT to those diminished by more than five orders of magnitude, with the levels of diminished activities being dependent upon DNA structure (13, 14, 20, 23, 28 -30). The specific TREX1 disease-causing mutations can result in either diminished catalytic function or altered post-translational modification and cellular localization (20,23,31). These varied effects exhibited by TREX1 mutant enzymes on catalytic function and cellular localization might be reconciled with the diversity of human disease pathogenesis to help explain the precise role of TREX1 in DNA degradation to prevent inappropriate immune activation.…”
Section: D200hmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the genes implicated include TREX1; SAMHD1; RNASEH2A, B and C; and ADAR1, with recent studies documenting activation of the IFN-I pathway in patients with mutations in ADAR1, responsible for editing of noncoding RNA, and in 90% of AGS patients overall [4, 6]. Variations in these same genes have also been associated with some cases of SLE, although the specific mutations or common variants tend to be distinct from those that account for AGS [7]. …”
Section: Genetic Associationsmentioning
confidence: 99%
“…Different TREX1 mutations have been reported in AicardiGoutière syndrome [11], systemic lupus erythematosus [12] and familial chilblain lupus [13]. These latter mutations involve the enzymatic sites of the protein, leading to exonuclease dysfunction and possibly causing the accumulation of aberrant DNA [14] or post-translational modification through ubiquitination [15].…”
Section: Introductionmentioning
confidence: 99%